Anammox biofilm system under the stress of Hg(II): Nitrogen removal performance, microbial community dynamic and resistance genes expression - Chen, Zhao; Zhang, Xiaojing; Ma, Yongpeng; Song, Yali; Li, Yingzhe; Geng, Guanglei; Huang, Yaning (Journal of hazardous materials, 2020)
[Display omitted] •AAOB could completely resist Hg(II) in concentrations (≤ 10 mg L−1).•Hg(II) in 20 mg L−1 could lower the TNRE to approximately 55 %.•The secretion of EPS helped AAOB resist the invasion of Hg(II).•Hg(II) induced the amplification of merA, merB, merD and merR. The existence of heavy metals in wastewater has obtained more attention due to its high toxicity and non-degradability. In this study, we investigated the changes of anaerobic ammonium oxidation (Anammox) system under long-term invasion of Hg(Ⅱ). The results indicated that the total nitrogen removal efficiency (TNRE) dropped to around 55 % as Hg(Ⅱ) concentration went up to 20 mg L−1. But the functional bacteria rapidly developed some resistant abilities and maintained a stable TNRE of 65 % till the end of test. The maximum relative expression fold change of merA, merB, merD and merR were 468.8476, 23.7383, 5.0321 and 15.2514 times, respectively. The high positive correlation between the expression abundance of metal resistance genes and the concentrations of Hg(Ⅱ) revealed the resistant mechanisms of microorganisms to heavy metals. Moreover, the protective strategy based on extracellular polymeric substances also contributed to the stability of Anammox system.